Investigation of the Formal Seed Supply Chain and Contribution of Seed Supplier Development to Improving the Seed Supply Chain in Nigeria - Samson, Amboge (Curtin University, 2022)
Agricultural productivity in Nigeria is low, predominantly attributed to low-quality seeds. Most farmers do not utilise formal seeds, which supply high-quality seed. Quality-seed availability, affordability, and accessibility challenges contribute to low adoption. A seed supply chain framework is proposed in this research to mitigate the challenges. Also, the proposed supplier development program will deliver adequate seed to farmers and increase the use of formal seed to increase farmers' productivity in low and medium countries.